Os “corpos em aliança” nas intersecções entre o coletivo musical Teto Preto e o contexto da festa Mamba Negra (PerCursos, 2024)
The present article aims to analyze how “bodies in alliance” occur at the intersections between the text of the musical collective Teto Preto and the context of the party Mamba Negra. After a brief presentation of the object of analysis, we present the main aspects of Judith Butler’s “performative theory of assembly”, which constitute our critical repertoire. Subsequently, from the methodological perspective of performance studies, we conduct an analysis of selected materials from Teto Preto’s performance, articulating them with the performative conditions of Mamba Negra. As a result, we highlight how the group vocalizes the context of the party, particularly regarding the union of vulnerable bodies in the struggle for political recognition. Furthermore, we highlight the political strategy of creating spaces aimed at the emergence of these bodies which, in coalition, establish bons of mutual recognition that strengthen them in the pursuit of less precarious lives. Mamba Negro and Teto Preto, thus, exemplify a political action stemming from collectively built and interdependent structures, akin to the “assembly” format discussed by Butler, which occurs not only in the street protests and their political demands, but also in spaces such as parties and other forms of entertainment like popular music, dance, and audiovisual products.
Keywords: performance studies; popular music; politics; Teto Preto; Mamba Negra